2022
DOI: 10.1101/2022.08.17.504255
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dimeric G-quadruplex motifs-induced NFRs determine strong replication origins in vertebrates

Abstract: Replication of vertebrate genomes is tightly regulated to ensure accurate duplication, but our understanding of the interplay between genetic and epigenetic factors in this regulation remains incomplete. Here, we investigated the involvement of three elements enriched at gene promoters and replication origins: guanine-rich motifs potentially forming G-quadruplexes (pG4s), nucleosome-free regions (NFRs), and the histone variant H2A.Z, in the firing of origins of replication. We show that two pG4s on the same DN… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…On the other hand, two G4-containing ORIs can drive DNA replication initiation in the chicken DT40 cell line (Valton et al, 2014, Prorok et al, 2019). More recently, Poulet-Benedetti et al (2023) found that two G4-forming motifs on the same strand are sufficient for replication initiation. According to this study, however, tandem G4s associated with ORIs tend to be located in NDR next to well-positioned nucleosomes, which is different from the GGN clusters studied here that are strongly associated with nucleosomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, two G4-containing ORIs can drive DNA replication initiation in the chicken DT40 cell line (Valton et al, 2014, Prorok et al, 2019). More recently, Poulet-Benedetti et al (2023) found that two G4-forming motifs on the same strand are sufficient for replication initiation. According to this study, however, tandem G4s associated with ORIs tend to be located in NDR next to well-positioned nucleosomes, which is different from the GGN clusters studied here that are strongly associated with nucleosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Several articles reported an association between ORIs and atypical DNA secondary structures formed by stacked arrangements of planar G-tetrads stabilized by Hoogsteen hydrogen bonding, called G-quadruplexes (G4) (Hansen et al, 2010; Cayrou et al, 2011; Besnard et al, 2012; Gindin et al, 2014; Valton et al, 2014; Smith et al, 2016; Prorok et al, 2019). While the role of G4s in ORI activity is still a matter of debate (Valton and Prioleau 2016; Akerman et al, 2020), a recent pre-print demonstrated that engineering dimeric G4 motifs in the same DNA strand is sufficient to induce the formation of a minimal ORI (Poulet-Benedetti et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…G4s have been implicated in a wide range of biological processes, including transcription (ref? ), telomere maintenance ( 24 ), DNA replication ( 25, 26 ) and repair ( 27, 28 ), and RNA processing and translation ( 29, 30 ). As regulatory elements, G4s act as molecular switches, modulating gene expression or protein-DNA associations ( 31, 32 ).…”
Section: Introductionmentioning
confidence: 99%